Distinguishing physical vs. chemical templating mechanisms for inducing graphitization in novolac matrix - Sandra N Ike; Randy Vander Wal (Carbon Trends)
Our previous work investigated the templating ability of graphene oxide-derived additives to induce graphitization of the novolac matrix. The findings led to two working hypotheses: the additives act as templates that promote matrix aromatic alignment to their basal planes during carbonization (referred to here as physical templating) in addition to forming radical edge sites that bond to the decomposing matrix (referred to here as chemical templating). However, results mainly underscored the role of functional groups on the GO additives (chemical templating). The aim of this current work seeks to differentiate the contributions of the operative mechanisms on graphitization. To study this, 2D materials with minimal oxygen functionalization, graphene and hexagonal boron nitride (hBN) were used as templates to induce graphitization of novolac matrix. First, the optimum weight percent of the 2D materials was determined with the composite graphitic quality measured by X-ray diffraction and Raman spectroscopy. Results revealed that hBN did not induce graphitization of novolac and was attributed to the absence of a sp² framework in hBN, unable to provide the crucial π-π interactions with the aromatic rings of the matrix. In contrast, the graphene additives mirrored one another and showed improved graphitization of the novolac. From these results, it was surmised that both mechanisms are operative; while physical templating offers control over long-range order in the form of crystallite height, chemical templating contributes to carbon reorganization and lateral growth extent.